2003
DOI: 10.1128/mcb.23.3.852-863.2003
|View full text |Cite
|
Sign up to set email alerts
|

Protein Kinase C Phosphorylates Ribosomal Protein S6 Kinase βII and Regulates Its Subcellular Localization

Abstract: The ribosomal protein S6 kinase (S6K) belongs to the AGC family of Ser/Thr kinases and is known to be involved in the regulation of protein synthesis and the G 1 /S transition of the cell cycle. There are two forms of S6K, termed S6K␣ and S6K␤, which have cytoplasmic and nuclear splice variants. Nucleocytoplasmic shuttling has been recently proposed for S6K␣, based on the use of the nuclear export inhibitor, leptomycin B. However, the molecular mechanisms regulating subcellular localization of S6Ks in response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
73
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(81 citation statements)
references
References 66 publications
(80 reference statements)
5
73
0
3
Order By: Relevance
“…In addition, our localization data showed that S6K2 is localized in the nucleus, while S6K1 is primarily cytoplasmic. Our finding of two functional S6Ks in Arabidopsis, one of which preferentially localized in the nucleus, is consistent with the animal systems where two isoforms of S6K (p70S6K and p85S6K) function exclusively in the cytoplasm and in nucleus, respectively (Koh et al, 1999;Valovka et al, 2003). Our interaction and phosphorylation data, taken together with the localization data, suggest that S6K1 is a functional ortholog of p70S6K and is likely to be regulated by the plant TOR pathway.…”
Section: Plant S6k Activity Appears To Be Regulated By the Tor Pathwaysupporting
confidence: 75%
“…In addition, our localization data showed that S6K2 is localized in the nucleus, while S6K1 is primarily cytoplasmic. Our finding of two functional S6Ks in Arabidopsis, one of which preferentially localized in the nucleus, is consistent with the animal systems where two isoforms of S6K (p70S6K and p85S6K) function exclusively in the cytoplasm and in nucleus, respectively (Koh et al, 1999;Valovka et al, 2003). Our interaction and phosphorylation data, taken together with the localization data, suggest that S6K1 is a functional ortholog of p70S6K and is likely to be regulated by the plant TOR pathway.…”
Section: Plant S6k Activity Appears To Be Regulated By the Tor Pathwaysupporting
confidence: 75%
“…In vitro data indicated that S6K2, not S6K1 or AKT, binds histone 3 and that this was dependent on the C-terminal nuclear localization signal in the S6K2 protein. On the other hand, growth factor stimulation of S6K2 induced phosphorylation of the C-terminal nuclear localizing signal, retaining active S6K2 in the cytoplasm (Valovka et al 2003). This indicates that S6K2 has active roles in the nuclear and in the cytoplasmic compartment, with possible involvement in proliferation.…”
Section: Discussionmentioning
confidence: 96%
“…The protein kinase CK2 phosphory-lates S6K1 at Ser 17 , and this signaling event induces nuclear export of S6K1 (29). Similarly, phosphorylation of Ser 486 located within the C-terminal nuclear localization sequence of S6K2 by protein kinase C leads to cytoplasmic retention of S6K2 (30). Known S6K functions in the nucleus include phosphorylation of the cAMP response element modulator CREM (31) and, more importantly, regulation of cap-dependent RNA splicing through S6K1 interaction with the SKAR (S6K1 Aly, Ref-like target) protein (25).…”
mentioning
confidence: 99%